Is reducing speed the right mitigating action to limit harmful emissions of seagoing RoRo cargo carriers? - Koos Frouws (Journal of Shipping and Trade (JST), 2016)
The Energy Emission Design Index (EEDI) is an index indicating the CO2 emission per transportation effort, for example the emitted tons CO2 per ton mile, to be calculated for each new design. The required index for new designs will be gradually lowered in the coming years resulting in either improved energy efficiencies or speed reductions.RoRo carriers are key stones in shore based logistical systems and as a result diverse in design speeds and main dimension ratio's. This diversity could be threatened by the relative simplicity of the EEDI regulations. This article aims to estimate the influence of the EEDI approach on 30 existing RoRo cargo carriers. The attained EEDI's per design are determined. Also the costs per transport effort are calculated based on the private costs and based on the social costs, both at the economically optimum speeds based on a uniformly applied sailing profile. The social costs are based on all emissions because the number of Environmental Special Area's is limited and the impact of speed reductions will not be limited to climate change. The expected speed reductions for these designs based on the EEDI, but also the required speed reductions when taking into account the total social costs are used to estimate the effectivity from the EEDI regulations. Amongst others it was concluded that the existing diversity in service speeds and main dimension ratio's will be jeopardized by the EEDI regulations.
Keywords: 650; EEDI; External costs; Economic performance; Vessel; Ship; RoRo; Design; Maritime technology; Maritime economic; Emissions; Sustainability; Level playing field